Enantioselective Synthesis of Chiral 1,2-Amino Alcohols via Asymmetric Hydrogenation of α-Amino Ketones with Chiral Spiro Iridium Catalysts - Yuan, Ming-Lei; Xie, Jian-Hua; Yang, Xiao-Hui; Zhou, Qi-Lin (Synthesis, 2014)
A highly efficient iridium-catalyzed asymmetric hydrogenation of α-amino ketones for the synthesis of chiral 1,2-amino alcohols is described. With chiral spiro iridium catalyst Ir-(R)-1c, a series of α-amino ketones were hydrogenated to chiral β-amino alcohols in excellent enantioselectivities (up to 99.9% ee) with TON up to 100 000. In addition, with this highly efficient method the chiral drugs (R)-clorpenaline and (R)-phenylephrine were prepared in very high efficiency.
Keywords: asymmetric hydrogenation; chiral spiro catalysts; amino ketones; amino alcohols; iridium catalysts